Why IT matters: An empirical study of e-business usage, innovation, and firm performance - Philipp Koellinger (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
The article argues that IT continues to have strategic relevance for companies because it enables innovation. A conceptual link between the adoption of IT and innovation is established. This conceptual link allows a market-based, economic explanation for variations in IT payoffs among firms: The successful adoption of new IT leads to innovation. Depending on the behavior of customers and competitors, a successful innovation can enable companies to gain competitive advantages. The economic theory of innovation suggests conditions that are necessary for firms to benefit from innovative activities. The relevance of IT as an important enabler of innovation is demonstrated using a very large sample of enterprises from different industries and countries in the European Union surveyed in late 2003. It is shown that a substantial share of firms use IT to introduce new processes into their business, or to offer new products or services to their customers. To study the relationship between firm performance and innovation, I estimate an error component model that controls for unobserved market-specific effects and various firm-specific characteristics. The regression results indicate that innovative firms are generally more likely to exhibit increasing turnover and employment. In addition, firms that conduct product or service innovations are also more likely to be profitable. Furthermore, enterprises using IT to innovate perform at least as well as those innovating without IT. Yet, no significant relationship between process innovation and profitability is found, suggesting that firms might have problems to appropriate excess profits from process innovations, independent from whether they are enabled by IT or not. Possible reasons for this include time-lags between process innovations and profit gains, problems to effectively protect process innovations from imitation by competitors, or a lack of complementary resources. The results suggest that the returns to IT critically depend on whether and how IT investments are transferred into innovative activities. In addition, they suggest that IT will maintain its strategic importance as long as the IT industry remains innovative in developing new IT hardware and useful new business applications for it.
Keywords: C25; L0; 330; Firm Performance; Innovation; Information Technology; Fixed Effects Logit